What's bred in the bone: Transference and Countertransference in Teachers - John Sherry; Leslie Warner; Andrew Kitchenham (Brock University, 2021)
Countertransference and transference have been well researched in the context of the client-therapist relationship, but there are few studies looking at these unconscious processes in other helping professions, such as teaching. Utilizing a hermeneutic phenomenological methodology, we investigated how transference and countertransference are understood and experienced by classroom teachers. We interviewed four school teachers on their understanding and management of the two concepts in the classroom and arrived at the following themes derived from the transcribed interviews for transference and countertransference, respectively: Schema, Relationship, Context, Unconscious; Background experience, Self-awareness, Self-reflection. We conclude with implications for teachers and counsellors, alike.